2017
DOI: 10.20473/amnt.v1i3.2017.243-251
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Riwayat Penyakit Diare dan Praktik Higiene dengan Kejadian Stunting pada Balita Usia 24-59 Bulan di Wilayah Kerja Puskesmas Simolawang, Surabaya

Abstract: ABSTRAKLatar belakang: Stunting pada anak merupakan dampak yang bersifat kronis dari konsumsi diet berkualitas rendah yang terus menerus dan didukung oleh penyakit infeksi dan masalah lingkungan. Praktik higiene yang buruk dapat menyebabkan balita terserang penyakit diare yang nantinya dapat menyebabkan anak kehilangan zat-zat gizi yang penting bagi pertumbuhan. Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan riwayat penyakit diare dan praktik higiene dengan kejadian stunting pada balita usia 24-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
30
0
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 18 publications
9
30
0
24
Order By: Relevance
“…This is in line with the previous research [11] showing that there was a relationship between the incidence of infectious diseases and the incidence of stunting (p-value 0.001). This study is similar to the other research result [21] describing that there was a significant relationship between the history of diarrhea and ARI with the incidence of stunting.…”
Section: The Relationship Between Infectious Disease Status Andsupporting
confidence: 92%
“…This is in line with the previous research [11] showing that there was a relationship between the incidence of infectious diseases and the incidence of stunting (p-value 0.001). This study is similar to the other research result [21] describing that there was a significant relationship between the history of diarrhea and ARI with the incidence of stunting.…”
Section: The Relationship Between Infectious Disease Status Andsupporting
confidence: 92%
“…According to Checkley et al (2008), 25% of stunting cases in children below two years old is associated with diarrhea. The same conclusion is confirmed by a study conducted in East Java where it is found that diarrhea and poor hygienic behavior are significantly related to stunting (Desyanti & Nindya, 2017). When repeatedly experiences diarrhea, a child has higher possibility to be stunted.…”
Section: Introductionsupporting
confidence: 59%
“…Studies on early childhood bring about persistent findings that sanitation behavior is a risk factor of stunting (Danaei et al, 2016;Desyanti & Nindya, 2017;George et al, 2016;Torlesse, Cronin, Sebayang, & Nandy, 2016). To maintain adequate environmental health during early childhood development, communities need to pay attention to a number of measures of sanitation behavior, that include stop defecating in the open, the use of environmental-friendly latrines with anti-leak and regularly-emptied septic tanks, cleaning toilet area, and safely disposal of children feces and used pampers.…”
Section: Sanitation Behavior and Risk Of Stunting … (Silva Liem)mentioning
confidence: 99%
“…Hal tersebut juga sangat memengaruhi derajat kesehatan lingkungan dan dapat mengakibatkan anak mudah terkena penyakit menular akibat air yang digunakan maupun lalat yang beterbangan di lingkungan mereka, sehingga akhirnya membuat anak-anak mereka mengalami stunting. Hal tersebut sesuai dengan penelitian Desyanti & Nindya (2017) yang menyatakan sebagian besar balita stunting mengalami kejadian diare yang sering yaitu lebih dari dua kali dalam tiga bulan terakhir, sedangkan pada kelompok tidak stunting sebagian besar jarang mengalami diare 25 .…”
Section: Hubungan Kualitas Perilaku Penghuni Terhadap Kejadian Stuntingunclassified